Textbook of veterinary anatomy - Dyce, K. M. (Keith M.) (Saunders, 2002)
This clinically-oriented text covers the anatomy of all major species of domestic animals. It provides the general knowledge of mammalian structure that is crucial to the understanding of the other basic sciences, as well as the more detailed information that is directly applicable to the practice of veterinary medicine. Discussing the various body systems, it then offers a working knowledge of them by addressing the regional anatomy of a particular species or group of species.